Volunteer Food Handlers’ Safety Knowledge and Practices in Implementing National School Nutrition Programme in Gauteng North District, South Africa - Paul K. Chelule; Mavis Ranwedzi (Safety, 2022)
Volunteer food handlers (VFHs) working in school feeding programmes contribute immensely to the safety of food served to the school learners. However, their level of knowledge and practice of safe food handling is questionable. This study investigated food safety knowledge and practices of VFHs working for the National School Nutrition Programme (NSNP) in Gauteng North District, South Africa. This was a descriptive quantitative study in which data were obtained using a standard structured questionnaire. A total of 115 VFHs participated in the study. Most of the VFHs (n = 84, 73.0%) had secondary education with working experience of between 1 to 12 months. Although a high level of knowledge on food safety was demonstrated by the VFHs, this did not fully translate into safe food handling practices. The new VFH recruits were 66% more likely to wear protective clothing than the rest (OR: 0.34, 95%CI: 0.12–0.91, p = 0.033). Women were 90% more likely to wear aprons than men (OR = 0.11; 95 CI: 0.03–0.45; p = 0.002). In this study, VFHs demonstrated adequate levels of knowledge on food safety. Lack of facilities contributed to VFH non-compliance to safe food handling practices. Thus, there is a need to further support VFHs to comply with recommended safe food handling practices.